Airway surface dehydration aggravates cigarette smoke-induced hallmarks of COPD in mice - Seys, Leen J.M.; Verhamme, Fien M.; Dupont, Lisa L.; Desauter, Elke; Dürr, Julia; Seyhan Agircan, Ayca; Conickx, Griet; Joos, Guy F.; Brusselle, Guy G.; Mall, Marcus A.; Bracke, Ken R. (PLOS ONE, 2015)
Introduction Airway surface dehydration, caused by an imbalance between secretion and absorption of ions and fluid across the epithelium and/or increased epithelial mucin secretion, impairs mucociliary clearance. Recent evidence suggests that this mechanism may be implicated in chronic obstructive pulmonary disease (COPD). However, the role of airway surface dehydration in the pathogenesis of cigarette smoke (CS)-induced COPD remains unknown. Objective We aimed to investigate in vivo the effect of airway surface dehydration on several CS-induced hallmarks of COPD in mice with airway-specific overexpression of the β-subunit of the epithelial Na+ channel (βENaC). Methods βENaC-Tg mice and wild-type (WT) littermates were exposed to air or CS for 4 or 8 weeks. Pathological hallmarks of COPD, including goblet cell metaplasia, mucin expression, pulmonary inflammation, lymphoid follicles, emphysema and airway wall remodelling were determined and lung function was measured. Results Airway surface dehydration in βENaC-Tg mice aggravated CS-induced airway inflammation, mucin expression and destruction of alveolar walls and accelerated the formation of pulmonary lymphoid follicles. Moreover, lung function measurements demonstrated an increased compliance and total lung capacity and a lower resistance and hysteresis in βENaC-Tg mice, compared to WT mice. CS exposure further altered lung function measurements. Conclusions We conclude that airway surface dehydration is a risk factor that aggravates CS-induced hallmarks of COPD.
Gesehen am 17.06.2020